2009
DOI: 10.1166/jnn.2009.029
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Strain Measurements of Ge(Si)/Si(001) Islands by HRTEM

Abstract: The distributions of the composition and the strain in the Ge(Si)/Si(001) coherent islands grown by molecular-beam epitaxy are investigated by digital analysis of high resolution transmission electron microscopy (HRTEM) micrographs. Local composition and strain are obtained from the measurement of the lattice displacement based on the Poisson's formula and Vegard's law. The analysis suggests that the islands have high Ge content at the island's central region. The island is partially relaxed by the substrate d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Accordingly, the Ge concentration on the top of QDs is as high as 65%. After 2 min etching, the Ge concentration at the center of the QDs is estimated to be 50%, which is still higher than the surface Ge concentration of 39% of the QDs grown at 680 • C. The symmetric shell structure in Ge distribution was also observed previously, but only for the low-temperature grown SiGe QDs [24][25][26], which is consistent with our observation. It is the symmetric shell structure that ensures the QRs formed after Si capping are symmetric.…”
Section: Resultssupporting
confidence: 92%
“…Accordingly, the Ge concentration on the top of QDs is as high as 65%. After 2 min etching, the Ge concentration at the center of the QDs is estimated to be 50%, which is still higher than the surface Ge concentration of 39% of the QDs grown at 680 • C. The symmetric shell structure in Ge distribution was also observed previously, but only for the low-temperature grown SiGe QDs [24][25][26], which is consistent with our observation. It is the symmetric shell structure that ensures the QRs formed after Si capping are symmetric.…”
Section: Resultssupporting
confidence: 92%
“…To understand the detailed structure, high-resolution TEM (HRTEM) was employed and typical [110] zone-axis TEM results were shown in Figures 1(b)-(d). In Figure 1(b), stacking faults (SFs) could be clearly observed in the Ge matrix, in which a triplet periodicity of (111) Ge lattice spacing in the SFs was explicitly featured [16]. The formation of SFs might come from the strain accumulation of Mn doping and lattice-mismatched precipitates.…”
Section: Mn X Ge 1-x Thin Film Growth By Mbementioning
confidence: 98%
“…Many studies in the past aimed at understanding the influence of stressor components on the mobility enhancement. [1][2][3][4][5][6][7] For P MOSFET transistors, it has been reported that either a compressive stress contributed from SiGe alloy embedded in S/D regions or a compressive contact-etch-stop layer (CESL) is preferred in the Si channel direction. A silicon nitride film, used as the foregoing CESL, can possess gigapascal-order intrinsic stress dependent upon the management of deposition condition.…”
Section: Introductionmentioning
confidence: 99%